Heterocheilus floridensis sp. n. (Nematoda: Heterocheilidae) from the West Indian manatee Trichechus manatus (Trichechidae, Sirenia) in Florida, USA - Moravec, Frantisek; Bakenhaster, Micah D; Seyoum, Seifu; Tringali, Michael D (Folia parasitologica, 2024)
Morphological data are used to describe a new nematode species, Heterocheilus floridensis sp. n. (Heterocheilidae) from the digestive tract of the Florida manatee Trichechus manatus latirostris (Harlan) (Trichechidae, Sirenia) from Florida, USA. Examination by light and scanning electron microscopy revealed that the new species differs from the related Heterocheilus tunicatus Diesing, 1839 mainly by having dentigerous ridges on the inner surface of the lips, a median unpaired papilla located anterior to the cloaca, and a considerably larger body size. Sequence data for subunits I and II of mitochondrial cytochrome oxidase gene, 18S small subunit and 28S ribosomal RNA genes were provided for molecular characterisation of the new species. However, the current unavailability of homologous sequence data for congeneric specimens precluded a molecular assessment of the morphological species hypothesis, and ascaridoid phylogenetic hypotheses could not be advanced. Specimens of Heterocheilus sp. collected from the Antillean manatee Trichechus manatus manatus Linnaeus in Puerto Rico, on loan from the US National Museum of Natural History, were morphologically consistent with the new species, so apparently all congeneric nematodes reported from both subspecies of the West Indian manatee Trichechus manatus Linnaeus and previously identified as H. tunicatus belong rather to H. floridensis sp. n. Heterocheilus hagenbecki (Khalil et Vogelsang, 1932) Sprent 1980 is here considered to be a species inquirenda. A key to valid species of Heterocheilus Diesing, 1839 is provided.
Keywords: Animals; Trichechus manatus; Phylogeny; Sirenia; Nematoda; zvířata; hlístice; fylogeneze